HUBUNGAN PEMANFAATAN PERPUSTAKAAN JURUSAN SEJARAH SEBAGAI SUMBER BELAJAR DENGAN HASIL BELAJAR MAHASISWA PENDIDIKAN SEJARAH ANGKATAN 2012 - Widodo, Ali (Indonesian Journal of History Education, 2015)
To achieve quality learning outcomes of students, it can use a library. The library is a center of academic facilities that provide library materials in the form of printed and non-printed, therefore, the library is an important learning resources on campus and fully utilized by the NII students. This study uses a quantitative approach with a descriptive correlational method (correlational study) were examined two or more variables .. In this study, researchers wanted to see the relationship between two variables without changing or conduct treatment of these variables. Population of this research are students who intensity the highest utilization in the first semester.